Project-Based Marine Thematic Learning In Early Childhood - Farida Samad; Rita Samad; Nurhamsa Mahmud (PT Mattawang Mediatama Solution, 2023)
Thematic learning is a characteristic of early childhood education. The principle of thematic learning is child-centered and the needs of children. This study aims to analyze project-based marine thematic learning in early childhood. The research method used is qualitative. The participants of this study were the principal and students of group B PAUD Pembina 1 Ternate. The data collection was a direct observation, in-depth interviews, and documentary methods. Data analysis used the transcript of the interview results followed by coding to find research focus on project-based marine thematic learning. Data analysis in this study used taxonomic analysis. The results revealed that teachers in group B had implemented project-based thematic learning. Some obstacles met by teachers in composing daily lesson plans. The teachers had difficulty integrating play activities with marine education-based learning related to school conditions, learning models, and media used in the marine education-based learning process. The teacher's effort in overcoming these problems is that teachers continue to apply marine thematic learning to students as a generation living in archipelagic areas.